Field measurement studies on thermal comfort in an air-conditioned cafe / Nor Nazatul Ashiqen Rashdi, Fairus Muhamad Darus and Rabiatul Adawiyah Nasir - Rashdi, Nor Nazatul Ashiqen; Muhamad Darus, Fairus; Nasir, Rabiatul Adawiyah (College of Built Environment, 2023)
Cafes have become popular social gathering spots as well as a "third space" for relaxation, socialising, and work, particularly among young customers.